An injectable liposome-anchored teriparatide incorporated gallic acid-grafted gelatin hydrogel for osteoarthritis treatment - Li, Guoqing; Liu, Su; Chen, Yixiao; Zhao, Jin; Xu, Huihui; Weng, Jian; Yu, Fei; Xiong, Ao; Udduttula, Anjaneyulu; Wang, Deli; Liu, Peng; Chen, Yingqi; et al. (Nature communications, 2023)
Intra-articular injection of therapeutics is an effective strategy for treating osteoarthritis (OA), but it is hindered by rapid drug diffusion, thereby necessitating high-frequency injections. Hence, the development of a biofunctional hydrogel for improved delivery is required. In this study, we introduce a liposome-anchored teriparatide (PTH (1–34)) incorporated into a gallic acid-grafted gelatin injectable hydrogel (GLP hydrogel). We show that the GLP hydrogel can form in situ and without affecting knee motion after intra-articular injection in mice. We demonstrate controlled, sustained release of PTH (1–34) from the GLP hydrogel. We find that the GLP hydrogel promotes ATDC5 cell proliferation and protects the IL-1β-induced ATDC5 cells from further OA progression by regulating the PI3K/AKT signaling pathway. Further, we show that intra-articular injection of hydrogels into an OA-induced mouse model promotes glycosaminoglycans synthesis and protects the cartilage from degradation, supporting the potential of this biomaterial for OA treatment. Osteoarthritis is a common disease that causes pain and difficulty moving joints. Here the authors present an injectable gelatin-based hydrogel that slowly releases teriparatide drug to avoid frequent injections, offering a potential solution for patients with osteoarthritis.